964 MOUTHCARE MATTERS: QI PROJECT TO IMPROVE ORAL HEALTH IN ELDERLY HOSPITAL INPATIENTS. (14th June 2022) - Daniel, C; Gaunt, V
Abstract: Background: A quality improvement (QI) project completed over four months on an elderly-care ward comprising 34 inpatients in a UK district general hospital. The QI team comprised the ward Foundation Year 1 (FY1) and Consultant, with Nursing staff consultation. Introduction: There is evidence that oral-health in elderly people deteriorates with hospitalisation (Terezakis et al. J Clin Periodontol. 2011;38(7):628–636). Poor oral-health is associated with increased incidence of hospital-acquired infections and reduced oral intake (Kaneoka et al. Infect Control Hosp Epidemiol. 2015;36(8):899–906; Poisson et al. Gerodontology. 2016;33(2):61–168). We had no data on oral-health among our hospital inpatients, nor on nursing measures to maintain or improve it. We aimed to collect baseline data and implement ward-based improvements to oral-health assessment and care. Method: Interventions were identified using a 'drivers-for-change' flow-diagram: main interventions were introduction of a mouthcare proforma (for nurse-led assessment of patient oral-health and documentation of mouthcare given), ensuring availability of mouthcare products and providing relevant ward-staff education. Two 'Plan-Do-Study-Act' cycles were completed; intervention implementation was staggered two-monthly, following evaluation of preceding changes' impact. Data to measure impact of changes was collected two-monthly by the FY1 on patient oral-health (subjectively scored with assessment tool), rate of proforma completion and patient-reported completion of routine mouthcare. Results: Over the four-month period, there were significant improvements to rates of oral-health assessment (proforma completion increased by 86%), completion of routine mouthcare (increased by 32%), and overall patient oral-health: proportion of 'good' or 'excellent' oral-health scores increased from 21% to 66%. We aim to deliver further ward-based education to maintain progress. Conclusion: These interventions are simple, low-cost and could be implemented across many elderly-care wards. Wider adoption would improve mouthcare across larger patient-numbers, with potential benefit to both patient experience and morbidity. Ongoing education and integration of the proforma into existing ward 'patient-care-bundles' will promote sustained improvement.